1999
DOI: 10.1103/physrevb.60.4406
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effect on large magnetoresistance in the lower charge-density-wave transition ofNbSe3

Abstract: A large magnetoresistance appearing below the T c2 -CDW ͑charge-density wave͒ transition temperature in NbSe 3 has been studied under various pressures including pressure above the critical pressure where the T c2 -CDW phase is suppressed totally. The large magnetoresistance appears as long as the T c2 -CDW phase exists. However, when the phase is suppressed totally by high pressure, neither large magnetoresistance nor any anomalies are induced by the magnetic field up to 12 T, suggesting that it is negative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…16 In contrast, this phenomenon is suppressed by pressure in NbSe3 and Ba1-xRxIrO3, in which a magnetic field enhances the resistance anomaly associated with the formation of the lower CDW state. 17,18 TCDW1 further increases to 235 K at 2.8 GPa and then is no longer evident.…”
Section: B Electronic Transportmentioning
confidence: 95%
“…16 In contrast, this phenomenon is suppressed by pressure in NbSe3 and Ba1-xRxIrO3, in which a magnetic field enhances the resistance anomaly associated with the formation of the lower CDW state. 17,18 TCDW1 further increases to 235 K at 2.8 GPa and then is no longer evident.…”
Section: B Electronic Transportmentioning
confidence: 95%
“…Typically, large negative MR occurs in thin-film metals [24], manganese based perovskites [25,26] and some disordered systems [27,28], while large positive MR has been observed in semiconductors [29] and semimetals [8,30]. In general, there exists only a few of CDW materials, which show large positive MR [31][32][33]. The origin of the huge positive MR effect in the CDW state is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…So the occurrence of the u-SC phase and the enhancement of T c by increasing pressure might be due to the decrease in the nesting size of the FS. For the T 1 -CDW phase, however, Yasuzuka et al 29,30) showed that the magnitude of a magnetoresistance due to a pressure-induced imperfect nesting of the T 1 -CDW phase under high pressure is much smaller than that of the T 2 -CDW phase. This observation shows that the FS near P 1 still keeps good nesting condition as compaired with the case of the T 2 -CDW state despite the u-SC transition temperature is higher than the l-SC one.…”
Section: Discussionmentioning
confidence: 98%